Case report: A follow-up report of omental packing and drug therapy for canine prostate adenocarcinoma - Li, Yanan; Li, Dapeng; Ma, Tianwen; Wei, Chengwei (Frontiers in Veterinary Science, 2024)
Canine prostate is susceptible to diseases such as cysts, abscesses, and tumors. A 15-year-old male castrated Chinese rural dog underwent staged treatment. Preliminary diagnosis is based on examination results, including clinical symptoms (tenesmus, dysuria, frequent urination, and hematuria); hematology (elevated neutrophil count); X-rays (swelling of the prostate); ultrasound examination (less uniform echo in the prostate region, no echo effect in parenchyma); biopsy smear of prostate tissue (large number of neutrophils and rod-shaped bacteria). Therefore, the dog was preliminarily diagnosed with a prostate abscess. Antibiotic therapy was used for treatment. Three days later, the symptoms of hematuria and frequent urination did not improve, and the state was poor. The owner was advised to undergo surgical treatment-omental packing. Meanwhile, bacterial culture identification, drug sensitivity test and histopathological examination were performed. Pathological diagnosis was prostate adenocarcinoma. Subsequently, antibiotic therapy with enrofloxacin and antineoplastic maintenance therapy with mitoxantrone were administered. Six months later, the dogs were followed up, and the results showed no disease in the prostate tissue and no metastatic lesions. This is the report describing the use of omental packing for the treatment of prostate adenocarcinoma in dogs. In order to provide an important theoretical basis for the treatment of prostate cancer - omental packing into veterinary routine.